Common presentation of an uncommon disease: a fatal acute aortic dissection in a young male - Sharlene Anjo; Ida Zarina Zaini (Pusat Perubatan Universiti Kebangsaan Malaysia, 2019)
Acute aortic dissection (AAD) is rare in the paediatric and young adult population. We present a fatal case of acute aortic dissection Stanford B in a young male diagnosed with hypertension. He presented with severe acute abdominal pain with malignant hypertension. He did not have any trauma to the chest or did not have history of an illicit drug abuse. He had no features suggestive of connective tissue disease as well as other typical signs of aortic dissection. The complain of acute, severe abdominal pain which was out of proportion and required multiple doses of intravenous opioid, raised the suspicion of aortic dissection in this case. Point of care sonography (POC) was done in Emergency Department (ED). However, due to its highly operator dependability, the intimal flap was missed. Computed tomography (CT) scan of abdomen was done and confirmed the diagnosis of AAD. Unfortunately, his clinical condition rapidly deteriorated few hours later with no response to surgical intervention and succumbed within 36 hours of admission. We highlighted the importance of the early recognition of this disease as well as the point of care sonography in ED as a diagnostic tool to tackle this time-sensitive disease.